Acute and sustained effects of a periodized carbohydrate intake using the sleep-low model in endurance-trained males - Riis, S.; Buch Møller, A.; Dollerup, O.; Høffner, L.; Jessen, N.; Madsen, K. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Repeated periodization of carbohydrate (CHO) intake using a diet-exercise strategy called the sleep-low model can potentially induce mitochondrial biogenesis and improve endurance performance in endurance-trained individuals. However, more studies are needed to confirm the performance-related effects and to investigate the sustained effects on maximal fat oxidation rate (MFO) and proteins involved in intramuscular lipid metabolism.